Asking the right question: implementation research to accelerate national non-communicable disease responses. (20th May 2019) - Peters, David H; Peters, Michael A; Wickramasinghe, Kremlin; Osewe, Patrick L; Davidson, Patricia M
Abstract : Non-communicable disease programmes can be strengthened by systematically identifying implementation challenges and translating them into questions that can be answered through appropriate research, say David H Peters and colleagues